On the Integration of Machine Agents into Live Coding. - Wilson, Elizabeth; Fazekas, György; Wiggins, Geraint (Organised Sound, 2023)
Co-creation strategies for human–machine collaboration have recently been explored in various creative disciplines and more opportunities for human–machine collaborations are materialising. In this article, we outline how to augment musical live coding by considering how human live coders can effectively collaborate with a machine agent imbued with the ability to produce its own patterns of executable code. Using machine agents allows live coders to explore not-yet conceptualised patterns of code and supports them in asking new questions. We argue that to move away from scenarios where machine agents are used in a merely generative way, or only as creative impetus for the human, and towards a more collaborative relationship with the machine agent, consideration is needed for system designers around the aspects of reflection, aesthetics and evaluation. Furthermore, owing to live coding's close relationship with exposing processes, using agents in such a way can be a useful manner to explore how to make artificial intelligence processes more open and explainable to an audience. Finally, some speculative futures of co-creative and artificially intelligent systems and what opportunities they might afford the live coder are discussed.